2009
DOI: 10.1371/journal.pone.0006168
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Voltage-Gated Potassium Channels in Human Neural Progenitor Cells

Abstract: BackgroundVoltage-gated potassium (Kv) channels are among the earliest ion channels to appear during brain development, suggesting a functional requirement for progenitor cell proliferation and/or differentiation. We tested this hypothesis, using human neural progenitor cells (hNPCs) as a model system.Methodology/Principal FindingsIn proliferating hNPCs a broad spectrum of Kv channel subtypes was identified using quantitative real-time PCR with a predominant expression of the A-type channel Kv4.2. In whole-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 66 publications
3
48
0
Order By: Relevance
“…First, we conducted MTT assays to determine if blocking Kv channels using TEA affected cell viability. MTT assays showed that cell viability was not significantly different following a 24 h treatment of cells with 10 mmol/L TEA, a concentration known to effectively block Kv channels [15] . We also tested the effects of TEA treatments of longer duration, performing MTT assays on cells incubated with 10 mmol/L TEA for 1, 3, 6, 9, and 12 d. In each of these time periods, TEA significantly decreased cell viability; these effects were compensated for the following experiments.…”
Section: Measurement Of Membrane Potential On Adipogenic Differen Tiamentioning
confidence: 97%
See 2 more Smart Citations
“…First, we conducted MTT assays to determine if blocking Kv channels using TEA affected cell viability. MTT assays showed that cell viability was not significantly different following a 24 h treatment of cells with 10 mmol/L TEA, a concentration known to effectively block Kv channels [15] . We also tested the effects of TEA treatments of longer duration, performing MTT assays on cells incubated with 10 mmol/L TEA for 1, 3, 6, 9, and 12 d. In each of these time periods, TEA significantly decreased cell viability; these effects were compensated for the following experiments.…”
Section: Measurement Of Membrane Potential On Adipogenic Differen Tiamentioning
confidence: 97%
“…The hMSCs were seeded into 96-well plates (20 000 cells/well) and, after growing for 12 h in AM containing 20% FBS, were serum-starved by culturing for 24 h in AM containing 2% FBS. Cells were then switched to 20% FBS supplemented with 10 mmol/L TEA for 24 h. MTT assays were performed as previously described [15] . Untreated cells were used as controls.…”
Section: Cytotoxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…During brain ontogenesis, potassium regulates proliferation of neural progenitors (21,39,40) and is maintained in heightened levels in rapidly dividing cells (41,42). As potassium currents also support the migration of early neurons over long distances due to cellular volume change (43), we can speculate from our data that potassium could be important to maintain mitotic activity at 30-days old organoids and to promote cell migration at 45-days old organoids, amongst other roles.…”
Section: Implications Of Trace Elements Detected In Cerebral Organoidmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] Moreover, the sequence diversity of ion channels, even within channel families, as well as their often multi-subunit complex three-dimensional structures provide the potential for the development of drugs that are highly selective for specific channel isoforms expressed at discrete stages of neurogenesis. This approach may be advantageous over infusion of growth factors or other bioactive peptides that are likely to have more widespread, pleiotropic effects across neuronal development.…”
Section: Introductionmentioning
confidence: 99%